Rancang Bangun Sistem Manajemen Gudang Terintegrasi Barcode Berbasis Web - anisa, efi (JATISI, 2025)
This study aims to design and develop a web-based warehouse management system integrated with a barcode scanner at PT Sarana Prima Logistindo. The background of this research lies in the company’s manual warehouse management process, which causes difficulties in tracking stock, data recording errors, and slow inbound and outbound processes. The system was developed using the waterfall method, consisting of requirement analysis, system design, implementation, testing, and maintenance stages. It was built using the PHP programming language with the CodeIgniter 3 framework, a MySQL database, and integrated barcode scanning technology to enhance efficiency and data accuracy. The research results show that the developed system can record stock in real time, minimize input errors, speed up the validation process, and generate accurate reports for management decisions. Black box testing indicates a 95% success rate in terms of functionality and data accuracy. Therefore, the implementation of a web-based warehouse management system integrated with a barcode scanner proves effective in improving operational efficiency, data accuracy, and supporting managerial decision-making at PT Sarana Prima Logistindo.